Historical and projected impacts of climate change and technology on soybean yield in China. (December 2022) - Guo, Shibo; Zhang, Zhentao; Guo, Erjing; Fu, Zhenzhen; Gong, Jingjin; Yang, Xiaoguang
Abstract: CONTEXT: Increasing soybean yield is essential for China. In order to secure the desire soybean yield gains, it is important to understand how changes in climate and technology impact soybean yield. OBJECTIVE: First, we used historical climate and specific technology data assessed the impact of historical climate and technology on soybean yield in China. Second, combined with the historical yield linear trends, we projected future soybean yield under climate change and technology improvement. METHODS: We collected the historical climate data (daily maximum and minimum temperatures, precipitation, and solar radiation) and actual crop data (soybean yield and agricultural management practices: sowing date, total agricultural machinery, effective irrigation area, pesticide application amount, and rural labor force) of 1312 soybean-growing counties in China from 1990 to 2017. Besides, we calibrated and validated the vegetative and reproductive stages, and the yield formation process genetic parameters of soybean of different maturity groups in DSSAT-CROPGRO-Soybean model by a five-year cycle based on soybean field experiment data. We defined agricultural management practices and genetic parameters as technology, and used Bayesian methods to conduct an impact assessment of historical climate and technology changes on soybean yield. We also projected soybean yield from 2021 to 2100 under climate change and different cases of technology improvement. RESULTS AND CONCLUSIONS: From 1990 to 2017, more than 90% of the study counties showed an increase in soybean yield, although the yield increase slowed down after 2010. Agricultural management practices and genetic parameters changes increased soybean yield by 16% (−24 to 50%) and 6% (−14 to 24%), respectively, while climate change decreased soybean yield by 1% (−14 to 18%). The positive impacts of agricultural management practices were mainly attributed to pesticide application amount and total agricultural machinery. With changes in agricultural management practices alone, soybean yield showed a plateau or even a decrease after 2010. If the technology remains at the level it was in 2010s, soybean yield would decrease in the future in 49% of the counties. SIGNIFICANCE: Based on climate, soybean yield, specific agricultural management practices and genetic parameters data, we quantified the impacts of historical climate and technology on soybean yield in China. Besides, we projected future soybean yield under climate change and different cases of technology improvement, and discussed possible solutions for future increasing soybean yield. This work has practical significance for understanding climate and technology impacts on soybean yield, and implementing countermeasures to address future climate change and increase yield. Graphical abstract: Unlabelled Image Highlights: Understanding how changes in climate and technology impact soybean yield is essential for China. The study aimed to assess the impact of climate and technology on soybean yield, and project future soybean yield. Bayesian methods, and climate, soybean yield, agricultural management practices and genetic parameters data were used. Historical technology increased soybean yield, however, yield in 49% counties would decrease in future if technology level remains as 2010s. This work has practical significance for implementing countermeasures to address future climate change and increase yield.